Designing luminescent diimine-Cu(i)–phosphine complexes by tuning N-ligand and counteranions: correlation of weak interactions, luminescence and THz absorption spectra. Issue 6 (20th January 2022) - Sun, Zhen-Zhou; Zhu, Ning; Pan, Xun; Hu, Fu-Zhen; Wang, Guo; Yang, Yu-Ping; Qiu, Qi-Ming; Li, Zhong-Feng; Xin, Xiu-Lan; Liu, Jian-Ming; Li, Xiao-Qi; Jin, Qiong-Hua; et al.
Abstract : π–π stacking interactions and C–H⋯X (X = O, F) interactions formed by counteranions help to enhance the rigidity of these structures and further improve their luminescence quantum yields. Abstract : Herein, six new [Cu(N^N)(P^P)] +/0 complexes with different N-ligands and counteranions, [Cu2 (dmp)2 (bdppmapy)I2 ] (1 ), [Cu2 (dmp)2 (bdppmapy)(CN)2 ]·3CH3 OH (2 ), [Cu(dmp)(bdppmapy)](BF4 ) (3 ), [Cu(dmp)(bdppmapy)](ClO4 ) (4 ), [Cu(phen)(bdppmapy)](BF4 ) (5 ), and [Cu(phen)(bdppmapy)](ClO4 ) (6 ), have been synthesized and characterized (bdppmapy = N, N -bis[(diphenylphosphino)methyl]-2-pyridinamine, phen = 1, 10-phenanthroline, dmp = 2, 9-dimethyl-1, 10-phenanthroline). Single-crystal X-ray diffraction showed that different counteranions help to construct various stacking modes 1D–3D via weak interactions, such as π–π, C–H⋯π and C–H⋯X (X = F, O). Photophysical analysis showed they have yellow-green to yellow-orange emission within a range of 504–569 nm, and excellent photophysical properties with quantum yields from 2.6% (2 ) to 77% (4 ). In this study, these results indicate that the π–π stacking and C–H⋯X (X = O, F) weak interactions help to enhance the rigidity of these structures and further improve their luminescence quantum yields. In addition, we have explored the nature of the complexes emission mechanism through theoretical calculations. According to DFT/TD-DFT calculations, the luminescence behavior of the six complexes is ascribed to MLCT or (M + X)LCT. THz spectra were applied to explore the relationship between weak interactions and luminescence. These results have opened up a new direction in the characterization of the properties of luminescent materials.